2017
DOI: 10.1159/000458412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of PD-L1 Expression in Patients with Surgically Resected Non-Small-Cell Lung Cancer

Abstract: Background: Immunotherapy can become a crucial therapeutic option to improve the prognosis of patients with non-small-cell lung cancer (NSCLC). Here, we evaluated the impact of programmed cell death ligand-1 (PD-L1) expression in surgically resected NSCLCs. Methods: We estimated PD-L1 expression in 229 consecutive NSCLC specimens using rabbit polyclonal antibodies to human PD-L1 in a SP263 immunohistochemical assay and evaluated PD-L1 expression for potential associations with clinicopathological parameters an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 40 publications
1
24
1
Order By: Relevance
“…An association between PD‐L1 and molecular mutations in NSCLC has been investigated with conflicting results. Some studies have documented an association between PD‐L1 expression and molecular alterations, including EGFR mutations, KRAS mutations, and ALK translocations, whereas other studies have failed to find such correlations . Our study did demonstrate a significant correlation of PD‐L1 expression (PD‐L1 positivity, high PD‐L1 expression, and expression levels) with KRAS mutations but not with any other mutations.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…An association between PD‐L1 and molecular mutations in NSCLC has been investigated with conflicting results. Some studies have documented an association between PD‐L1 expression and molecular alterations, including EGFR mutations, KRAS mutations, and ALK translocations, whereas other studies have failed to find such correlations . Our study did demonstrate a significant correlation of PD‐L1 expression (PD‐L1 positivity, high PD‐L1 expression, and expression levels) with KRAS mutations but not with any other mutations.…”
Section: Discussioncontrasting
confidence: 61%
“…PD‐L1 expression has been observed to correlate with some clinicopathologic features, including smoking, an advanced tumor stage, and squamous cell carcinoma histology . However, other studies have failed to demonstrate such associations .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in a retrospective Japanese study, multivariate logistic regression identified squamous histology to be independently associated with a higher objective response rate with nivolumab (67 vs 11%; p = 0.004) [63]. As squamous histology has been found to be independently associated with high expression of PD-L1 [64], it is likely that PD-L1 expression rather than tumor histology may underlie any difference seen between squamous and nonsquamous populations, and therefore may be biasing post hoc analyses. Due to the influence of PD-L1 expression, not to mention the association between smoking status and histology type, and the insufficient evidence for a survival benefit in one population over another, we do not recommend using histology as a factor to select patients more likely to benefit from anti-PD-1/PD-L1 therapies.…”
Section: Tumor Histologymentioning
confidence: 93%
“…Though multimodal therapies are often used in patients with non-small cell lung cancer (NSCLC), the overall prognosis of NSCLC remains poor [3]. Immunotherapy is reported to be a relatively effective strategy for NSCLC treatment.…”
Section: Introductionmentioning
confidence: 99%